2020
DOI: 10.1155/2020/3683629
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Capacities of Hygroscopic Materials Based on NaCl-TiO2 and NaCl-SiO2 Core/Shell Particles

Abstract: Hygroscopic materials which possess high moisture adsorption capacity were successfully upgraded by the functionalization of sodium chloride (NaCl) using two nuances of oxides. A procedure was developed to first prepare submicron-sized NaCl crystals; thereafter, these crystals were coated by choice of either titanium dioxide (TiO2) or silica (SiO2) to enhance the hygroscopic properties of NaCl and prevent its premature deliquescence. After coating, several analytical techniques were employed to evaluate the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…They have a “J” format and are typical of crystalline materials such as sugars and salts which is the case with vegetable salt. In this case, moisture gain is very low to the point where crystals begin to dissolve in water absorbed on the crystal surface (deliquescence point) and as sodium chloride presents an RH 0 of .75, (Bermeo et al, 2020) our result can be explained by the fact that the RH 0 was lowered in this product due to the presence of amorphous ingredient. Ghorab et al (2014), studied the blend of crystalline sodium chloride with different percentages of an amorphous solid (maltodextrin) finding that individually sodium chloride presented an RH 0 of .75 but when blended with 40% of maltodextrin it would lower down to .71.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…They have a “J” format and are typical of crystalline materials such as sugars and salts which is the case with vegetable salt. In this case, moisture gain is very low to the point where crystals begin to dissolve in water absorbed on the crystal surface (deliquescence point) and as sodium chloride presents an RH 0 of .75, (Bermeo et al, 2020) our result can be explained by the fact that the RH 0 was lowered in this product due to the presence of amorphous ingredient. Ghorab et al (2014), studied the blend of crystalline sodium chloride with different percentages of an amorphous solid (maltodextrin) finding that individually sodium chloride presented an RH 0 of .75 but when blended with 40% of maltodextrin it would lower down to .71.…”
Section: Resultsmentioning
confidence: 58%
“…They have a "J" format and are typical of crystalline materials such as sugars and salts which is the case with vegetable salt. In this case, moisture gain is very low to the point where crystals begin to dissolve in water absorbed on the crystal surface (deliquescence point) and as sodium chloride presents an RH 0 of .75, (Bermeo et al, 2020) our result can be explained by the fact that the RH 0 was lowered in this product due to the presence of amorphous ingredient. It can also be seen that when the material is exposed to an environment of 90% RH, the moisture uptake increases with temperature, being under 50 g/100 g DM for 15 C and 25 C, but when temperature increases to 35 C and 45 C this value slightly overpasses 100 g/100 g DM.…”
Section: Model Equations and Adsorption Isothermsmentioning
confidence: 56%
“…Differences in moisture content exhibited in the current study might be due to dipping of fish into 5%–10% NaCl salt solution (in improved method) to avoid insect infestation in comparison to 10%–25% NaCl solution practiced in traditional method to get a higher weight benefit. The hygroscopic characteristics of NaCl salt bind with water in its structure (Bermeo et al., 2020 ), which results in a comparatively higher moisture content in the dried fish produced in that way. Irrespective of processing and packaging method, increasing moisture content was correlated with decreasing protein content during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The water uptake and swelling ratio shared a proportional relationship, where the sorption of water molecules causes dimensional expansion on the membrane, which is usually described by the term swelling ratio 87 . In the case of TiO 2 , Bermeo et al 91 reported a relative work on the adsorption capacities between SiO 2 and TiO 2 . The results demonstrate a high hygroscopic nature in TiO 2 compared with SiO 2 , where TiO 2 absorbs more water molecules.…”
Section: Resultsmentioning
confidence: 99%